Novel mesothelin antibodies enable crystallography of the intact mesothelin ectodomain and engineering of potent, T cell-engaging bispecific therapeutics - Lin, Ida; Rupert, Peter B.; Pilat, Kristina; Ruff, Raymond O.; Friend, Della J.; Chan, Man Kid; Clarke, Midori; Hoffstrom, Benjamin G.; Carter, Jane; Meshinchi, Soheil; Bandaranayake, Ashok D.; Mehlin, Christopher; et al. (Frontiers in Drug Discovery, 2023)
Mesothelin is a glypiated, cell-surface glycoprotein expressed at low levels on normal mesothelium but overexpressed by many cancers. Implicated in cell adhesion and multiple signaling pathways, mesothelin’s precise biological function and overall structure remain undefined. Antibodies targeting mesothelin have been engineered into immunotoxins, antibody-drug conjugates, CAR-T cells, or bispecific T cell engagers as candidate therapeutics but most face challenges, including binding epitopes that are not optimal for selected modalities. Here we describe the isolation and characterization of a novel anti-mesothelin antibody, 1A12, including crystallographic mapping of the 1A12 epitope in relation to other antibodies (amatuximab, anetumab). 1A12 possesses uniquely favorable properties, including a membrane-proximal epitope, and enabled structure determination of the complete mesothelin ectodomain. We incorporated 1A12 into two different bispecific T cell engaging architectures with various anti-CD3 co-targeting elements as candidate therapeutics, demonstrating in vitro functionality and potency.